Hydrothermal synthesis of SnQ (Q = Te, Se, S) and their thermoelectric properties. (16th October 2017) - Feng, Dan; Ge, Zhen-Hua; Chen, Yue-Xing; Li, Ju; He, Jiaqing
Abstract: Lead-free IV – VI semiconductors SnQ ( Q = Te, Se, S) are deemed as promising thermoelectric (TE) materials. In this work, we designed a hydrothermal route to selectively synthesize single phase SnTe, SnSe and SnS nanopowders. For all three samples, the phase structure were characterized by x-ray diffraction, SnTe particles with octahedron structure and SnSe/SnS particles with plate-like shape were observed by field emission scanning electron microscopy and transmission electron microscopy, the formation mechanism was discussed in detail. Then, SnTe, SnSe and SnS nanopowders were densified by spark plasma sintering for investigating TE properties. It was noticed that SnSe and SnS exhibited remarkably anisotropy in both electrical and thermal properties attributed to the layered crystal structure. The highest ZT values 0.79 at 873 K, 0.21 at 773 K, and 0.13 at 773 K were achieved for SnTe, SnSe and SnS bulk samples, respectively.